The new SOLPS-ITER code package - Wiesen, S.; Reiter, D.; Kotov, V.; Baelmans, M.; Dekeyser, W.; Kukushkin, A.S.; Lisgo, S.W.; Pitts, R.A.; Rozhansky, V.; Saibene, G.; Veselova, I.; Voskoboynikov, S. (Journal of nuclear materials, 2015)
The SOLPS-ITER package represents a renewed coupling of the up-to-date parallelized EIRENE Monte-Carlo code and the B2.5 edge plasma solver. Each part of the fluid-kinetic code system has been dismantled and analysed. For SOLPS-ITER, full backwards compatibility with previous SOLPS4.3 ITER reference simulations is critical. We present the results of the ongoing comprehensive benchmark activity and discuss how SOLPS-ITER can be tuned to reproduce ITER simulations performed with SOLPS4.3. In particular in SOLPS-ITER a quantitative “metric” to measure the level of code convergence has been implemented, with corresponding code diagnostics carried over from SOLPS4.3, allowing code run times to be accurately compared. Good agreement is found between the two codes in the tests so far. Remaining discrepancies in the solution in front of the divertor targets are likely related to different formulations of the equations and the different discretization schemes used by the codes.